2016
DOI: 10.1021/jacs.5b12659
|View full text |Cite
|
Sign up to set email alerts
|

A Transition from Localized to Strongly Correlated Electron Behavior and Mixed Valence Driven by Physical or Chemical Pressure in ACo2As2 (A = Eu and Ca)

Abstract: We demonstrate that the action of physical pressure, chemical compression, or aliovalent substitution in ACo2As2 (A = Eu and Ca) has a general consequence of causing these antiferromagnetic materials to become ferromagnets. In all cases, the mixed valence triggered at the electropositive A site results in the increase of the Co 3d density of states at the Fermi level. Remarkably, the dramatic alteration of magnetic behavior results from the very minor (<0.15 electron) change in the population of the 3d orbital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

26
84
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 66 publications
(111 citation statements)
references
References 33 publications
26
84
0
Order By: Relevance
“…We and others have previously demonstrated that above the critical pressure of 3.1 GPa the LP‐EuCo 2 P 2 phase transforms into the HP‐EuCo 2 P 2 phase, with the clear change in the oxidation state of Eu, which was also confirmed in the present experiments by the dramatic change in the XAS spectra observed at the Eu L 3 ‐edge (Figure a). Based on these spectral changes, Eu undergoes a nearly complete conversion from the +2 to +3 formal oxidation state.…”
Section: Figuresupporting
confidence: 89%
See 1 more Smart Citation
“…We and others have previously demonstrated that above the critical pressure of 3.1 GPa the LP‐EuCo 2 P 2 phase transforms into the HP‐EuCo 2 P 2 phase, with the clear change in the oxidation state of Eu, which was also confirmed in the present experiments by the dramatic change in the XAS spectra observed at the Eu L 3 ‐edge (Figure a). Based on these spectral changes, Eu undergoes a nearly complete conversion from the +2 to +3 formal oxidation state.…”
Section: Figuresupporting
confidence: 89%
“…Finally, we should point out that EuCo 2 As 2 also undergoes a pressure‐induced structural collapse with the critical pressure of ≈4.5 GPa at room temperature . In this compound, however, the change in the Eu oxidation state is not as drastic as seen in the case of EuCo 2 P 2 . We carried out XAS measurements on the L 3 ‐edge of Eu and K‐edges of Co and As and observed the same spectral changes as seen in EuCo 2 P 2 , albeit to a lesser extent (Figure S3).…”
Section: Figurementioning
confidence: 80%
“…As revealed by high-pressure XAS, the average valence state of Eu in both EuFe 2 As 2 and EuCo 2 As 2 increases with the applied pressure due to a part transition from Eu 2+ to Eu 3+ . However, the mean valence in them gets stabilized around +2.3 at 10 GPa and +2.25 at 12.6 GPa, for EuFe 2 As 2 and EuCo 2 As 2 , respectively 43, 44 . Therefore, the dip in T Eu ( P ) around 11 GPa in Fig.…”
Section: Discussionmentioning
confidence: 98%
“…However, such instances are still rare and the transition usually requires a very high pressure that is not easily accessible. [4][5][6] Starting from the discovery of graphene, 7 the field of two-dimensional (2D) materials has undergone rapid development in the past decade. Many new kinds of 2D materials have been proposed and fabricated, which exhibit a vast range of novel material properties, not seen in the usual 3D bulk materials.…”
mentioning
confidence: 99%